Bioactivity, Cytocompatibility and Effect of Cells on Degradation Behavior of Multiaxially Forged Ultrafine-grained Mg-2Zn-2Gd Alloy. Issue 2 (5th July 2019) - Trivedi, P; Nune, K C
Abstract : Magnesium alloys are most promising candidate to be next generation biomaterials due to their ability to degrade biologically under physiological environment. We elucidate here the structure-process-property relationship of Mg-2Zn-2Gd alloy with enhanced mechanical behavior for retaining the mechanical integrity during degradation. Furthermore, we studied the effect of degradation behavior in the presence of cells (seeding density: 10, 000 cells/cm 2 ). As-cast Mg-2Zn-2Gd alloy was subjected to heat treatment and multiaxial forging cycles, to produce different grain sizes. Microstructural and phase characterization was carried out by using SEM and X-ray diffraction respectively. The mechanical behavior as a function of grain size was studied through tensile tests. XRD and FTIR analysis were carried out to test the bioactivity of the samples after immersion in simulated body fluid (SBF), to confirm the coating phases and degradation product. The samples coated with apatite using a biomimetic approach used for degradation studies. Change in pH was monitored at regular intervals. The study underscores that the degradation rate was enhanced in the presence of cells due to metabolism activities of cell, which reduces formation of salt layer resulting in increased charge transfer from substrate to solution, which also led to higher drop in pH in the presence of cells. The study also revealed that ultrafine grained samples showed controlled degradation and enhanced cellular attachment, viability and higher fibronectin expressions in comparison to the coarse grain counterparts.